Carbono 21: Promoting Forestation Through Digital Assets - Correia, Pedro Henrique Barcha; Simplicio Junior, Marcos Antonio (Companion Proceedings of the Brazilian Symposium on Computer Networks and Distributed Systems (SBRC); 2025: Companion Proceedings of the 43rd Brazilian Symposium on Computer Networks and Distributed Systems, 2025)
Despite its environmental benefits, forestation is often overlooked in favor of more profitable crops with negative environmental impacts. In response, this work promotes forestation through tokenization, creating financial incentives for landowners who plant trees. Forested areas and green assets are transformed into Non-Fungible Tokens (NFTs) on a consortium blockchain. Their metadata is automatically updated via satellite-based deforestation tracking systems, something unseen in the literature. The solution also contributes to distributed systems and the environment by proposing several transparency mechanisms – often lacking in forestation efforts and permissioned blockchains –, enabling authorities to audit the transaction and utilization of green assets.